2020
DOI: 10.1161/jaha.119.014254
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging Estimation of Myocardial Iron Repletion Following Administration of Intravenous Iron: The Myocardial‐IRON Trial

Abstract: Background Intravenous ferric carboxymaltose ( FCM ) improves symptoms, functional capacity, and quality of life in heart failure and iron deficiency. The mechanisms underlying these effects are not fully understood. The aim of this study was to examine changes in myocardial iron content after FCM administration in patients with heart failure and iron deficiency using cardiac magnetic resonance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 27 publications
6
69
0
3
Order By: Relevance
“…1). After excluding 12 reports [6][7][8][9][10][11][12][13][14][15][16][17], mainly because they were not randomisedcontrolled trials or did not report relevant outcomes (Supplementary Table S1), seven trials (Table 1) that enrolled 2,166 patients (n = 1168 assigned to IV iron; n = 998 assigned to the control/placebo) were included in the primary analysis [4,[18][19][20][21][22][23]. The most common definition of ID was a ferritin < 100 µg/L and/or, if ferritin was 100-300 µg/L, a TSAT of < 20%.…”
Section: Resultsmentioning
confidence: 99%
“…1). After excluding 12 reports [6][7][8][9][10][11][12][13][14][15][16][17], mainly because they were not randomisedcontrolled trials or did not report relevant outcomes (Supplementary Table S1), seven trials (Table 1) that enrolled 2,166 patients (n = 1168 assigned to IV iron; n = 998 assigned to the control/placebo) were included in the primary analysis [4,[18][19][20][21][22][23]. The most common definition of ID was a ferritin < 100 µg/L and/or, if ferritin was 100-300 µg/L, a TSAT of < 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Mean ± standard deviation LVEF and RVEF were 40.3 ± 10.4% and 56.3 ± 11.4%, and median (inter‐quartile range) were 39% (33–47) and 58% (49–63), respectively. Detailed baseline characteristics of the patients in the two study groups have been reported elsewhere 12,16 . At enrolment, LVSD 1 and LVSD 2 were found in 27 (50.9%) and 38 (71.7%) patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At 30 days, patients assigned to placebo received intravenous FCM if ID persisted. The study design, protocol, and main results have been published and are available elsewhere 12,16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the unequivocal benefits of intravenous iron may be related to a peripheral effect [ 14 , 28 ], recent studies support a cardiac-centered hypothesis. First, ferric carboxymaltose administration was associated with cardiac iron repletion in cardiac magnetic resonance T2* and T1 mapping sequences [ 29 ]. Second, Doppler and strain rate echocardiography parameters were significantly improved after intravenous iron administration in patients with stable systolic HF and ID without anemia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%